2015
DOI: 10.4321/s0213-61632015000300002
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of complicated grief

Abstract: -Background and Objectives:In the discussion of apparent similarities between symptoms of grief and depression, research and theory have often confounded these two constructs because, as a construct, grief is distinct from depression and because these two constructs may have distinct trajectories. This study examines the trajectories of complicated grief and associated risks and the relationship between trajectories of complicated grief and depression.Design: Longitudinal. Setting: Intervention methods for enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Endurance, transient‐reaction, resilience, and prolonged‐symptomatic trajectories were identified for both PGD and depressive symptoms, whereas symptom trajectories of potential recurrence and chronic distress were uniquely identified for PGD and MDD, respectively. In addition, despite endurance and transient‐reaction trajectories conjointly comprising the most prevalent trajectories for PGD 16‐19 and depressive (see systematic review) 35 symptoms as reported, prevalence rankings of the other trajectories differed between PGD and depressive symptoms (Table 2). The prolonged‐symptomatic trajectory was the third and the least prevalent trajectories for depressive and PGD symptoms, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endurance, transient‐reaction, resilience, and prolonged‐symptomatic trajectories were identified for both PGD and depressive symptoms, whereas symptom trajectories of potential recurrence and chronic distress were uniquely identified for PGD and MDD, respectively. In addition, despite endurance and transient‐reaction trajectories conjointly comprising the most prevalent trajectories for PGD 16‐19 and depressive (see systematic review) 35 symptoms as reported, prevalence rankings of the other trajectories differed between PGD and depressive symptoms (Table 2). The prolonged‐symptomatic trajectory was the third and the least prevalent trajectories for depressive and PGD symptoms, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Construct distinctiveness of PGD and MDD has been established by confirmatory factor analysis, 12 bifactor analysis, 13 incremental validity testing for PGD's significantly increasing the explained variance in quality of life above MDD, 14 and lower‐level mediation analysis to show that change in each construct predicts a considerably different amount of change in the variance of the other construct 15 . However, no research has yet compared how well the patterns of change (trajectories) for PGD and MDD symptoms synchronize during bereavement, despite the importance of the temporal frame in defining PGD and MDD, the well‐observed phenomenon that grief‐related distress symptoms resolve over time, 5,8 and the heterogeneity of grief reactions as shown by individually identified distinct symptom trajectories for PGD 8,16‐19 and MDD 16,20‐26 . Furthermore, among studies that identified distinct PGD‐ or MDD‐symptom trajectories, few covered early and late bereavement (1 or 3 months 8,18,22,24,25 and >18 months 16,18,25,26 post‐loss, respectively).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a lack of longitudinal studies that examine distinct patterns of grief in disaster-bereaved individuals and factors predicting the different trajectories. To date, two studies [24, 25] have examined different patterns of problematic grief over time after the loss due to natural causes. Djelantik et al [24] found four trajectories of PGD symptoms in bereaved individuals, using two time points, 6 and 18 months post loss: a persistent high PGD symptom-trajectory, a persistent moderate, a decreasing moderate and a persistent low PGD symptom-trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…In the study, the majority (90%) of individuals had lost a loved one due to a natural cause. In a similar study with one additional assessment at 12 months, Nam [25] identified two trajectories, a persistent high and a persistent low grief trajectory, in a sample of individuals who had lost a relative in dementia, mainly spouses.…”
Section: Introductionmentioning
confidence: 99%